1990
DOI: 10.1002/mrm.1910160114
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of glycogen storage disease by in vivo13C NMR comparison of normal volunteers with a patient

Abstract: Broadband proton-decoupled natural abundance 13C spectra of the human calf, liver, and head were obtained from normal volunteers and a patient with glycogen type IIIA storage disease. Two concentric and coplanar surface coils of diameters 8.0 cm and 13.0 cm were used for 13C (at 16.0 MHz) and 1H (at 63.6 MHz), respectively. A WALTZ-8 sequence lead to homogeneous decoupling over a large volume. In addition to lipid resonances a variety of other metabolite resonances could be resolved. The glycogen concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…Metabolic steady state is usually assumed, which means that total concentrations of the metabolic pools as well as metabolic fluxes are constant throughout the infusion experiment. Studies tracking the time evolution of the pool sizes, as possible with 1 …”
Section: Metabolic Flux Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolic steady state is usually assumed, which means that total concentrations of the metabolic pools as well as metabolic fluxes are constant throughout the infusion experiment. Studies tracking the time evolution of the pool sizes, as possible with 1 …”
Section: Metabolic Flux Analysismentioning
confidence: 99%
“…Given the limitations in 13 C detection in vivo in small volumes, 13 C MRS in mice was at first applied to tissue brain extracts with indirect detection [95]: these results gave a quantitative appreciation of neuroglial metabolism with their respective regional differences and distinction of GABAergic and glutamatergic neurotransmission. A first proof of concept of the feasibility of in vivo detection was made at 7 Tesla with a direct detection sequence applying 1 H polarization transfer to 13 C, combined to 1 H broadband localization [50] in a volume of interest of 175 mL [27].…”
Section: C Mrs In the Mouse Brain In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…The calcuwhich compares favorably with the 21:1 SNR reported for lated maximal SAR local (Eq. [3]) is within the FDA guide-5 min measurements at 4.7 T using a 3.5 cm 13 C coil (15). lines for local power deposition.…”
mentioning
confidence: 99%
“…Despite these drawbacks, conin that 1 H decoupling can increase spectral resolution, especially in the PME and PDE resonances at low magnetic centric coil design was not prohibitive for some clinical applications using small coils at 4.7 T (14) as well as at fields (1), and improved signal-to-noise ratio (SNR) can be obtained by NOE generation. These heteronuclear tech-1.5-2.1 T (15,16). However, for the volumes needed for human applications at 4 T, we found that the performance niques use relatively long and intense RF irradiation at the 1 H frequency, which can make it difficult to achieve decou-of the proton coil in a double concentric arrangement was not sufficient for decoupling within FDA guidelines.…”
mentioning
confidence: 99%